PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK WARALABA KEBAB TURKI BABA RAFI DI KOTA MATARAM - Phyta Rahima (Universitas Bumigora, 2017)
The tittle of this research is The Effect Of Marketing Mix to Customers’s Buying Decision at Kebab Turki Baba Rafi Franchise Product in Mataram. The Purpose of this research are to know The Effects of Marketing Mix to Customer’s Buying Decision at Kebab Turki Baba Rafi in Mataram not only simultantly but also partially and to know which one of Marketing Mix has dominant effect to Customer’s Buying Decision at Kebab Turki Baba Rafi franchise’s productin Mataram. The kind of this research is causality research. The data of this research are kuantitatif and kualitatif data. To answer the question, data is collected from 100 respondent who were asked to fill the questionaire about the research variables, Product, Price, Place, Promotion, People and Customer’s Buying Decision at Kebab Turki Baba Rafi in Mataram. Then t-test and f-test is used to test the data, beside that the researchers used validity and reliability test, and linear regression. The results of the t-test and f-test analysis shows that Promotion and Place to have a positive and significant impact on Customer’s Buying Decision at Kebab Turki Baba Rafi in Mataram. And the result of analysis show that 57.3% Y Variable explained by Independent Variable such as Product, Price, Place, Promotion and People and remain 42,7% explain by other variable out of used variable. Meanwhile, promotion and place have dominant effect to Customer’s Buying Decision at Kebab Turki Baba Rafi in Mataram. Based on the results, The all of question at quesionaire have a valid and reliable question which is used to get the data in this research